The presentation of noun class systems of Niger-Congo languages - (:unkn) unknown (My University, 2022)
The graphical presentation of Niger-Congo noun class systems shows considerable variation, which deserves a careful examination. The choices of presentation seem to depend on the mere fancy of authors: close languages may be presented in very different ways while different systems may be given very similar graphical choices. After consulting hundreds of descriptions of noun class languages of the Niger-Congo phylum, I could determine four major presentation types. This huge amount of information also allowed me to present new statistical data on the typology of the noun class systems of the phylum.
Keywords: African Research